A numerical investigation of a fixed bed CO2 adsorption process using Phase Change Materials. - Beraldo, Cleiton de Souza (2022)
Interest in adsorption in the context of Carbon Capture and Storage (CCS) has increased in recent years due to the low energy consumption required, as compared to the more well-established route of absorption. In order to reduce even more the energy required by adsorption and to increase the specific adsorption capacity, measures have been proposed to counteract the undesired exothermic behavior of adsorption processes, such as U-tubes inserted on the adsorption bed and phase change materials (PCM). The latter offers great potential of storing substantial amounts of energy. In this work, the aim is to analyze the behavior of a fixed bed CO2 adsorption system with PCM and provide a comprehensive interpretation to explain the phenomenon. The bed is filled with activated carbon or zeolite as adsorbent and paraffin wax as phase change material. The mathematical model for PCM in fixed bed proposed by Schumman, based on balances of mass and energy, has been modified to include the expressions of transport phenomena, thermodynamic equilibrium and adsorption kinetics. The model was validated with experimental data from literature and the results from the numerical solution were used to analyze the thermal performance of the charging mode of the adsorption process and. The studies revealed a increase of the theoretical CO2 adsorption in capacity by 10% in total volume of gas adsorbed, due to the reduction of the maximum temperature of the process by 2 ºC. To be the most effective, the heat transfer interval of the phase change material aligns with the adsorption breakthrough curve.